Preparation of Cd/Pb Chalcogenide Heterostructured Janus Particles via Controllable Cation Exchange - Zhang, Jianbing; Chernomordik, Boris D.; Crisp, Ryan; Kroupa, Daniel M.; Luther, Joseph M.; Miller, Elisa M.; Gao, Jianbo; Beard, Matthew C. (Acs Nano, 2015)
We developed a strategy for producing quasi-spherical nanocrystals of anisotropic heterostructures of Cd/Pb chalcogenides. The nanostructures are fabricated via a controlled cation exchange reaction where the Cd2+ cation is exchanged for the Pb2+ cation. The cation exchange reaction is thermally activated and can be controlled by adjusting the reaction temperature or time. We characterized the particles using TEM, XPS, PL, and absorption spectroscopy. With complete exchange, high quality Pb-chalcogenide quantum dots are produced. In addition to Cd2+, we also find suitable conditions for the exchange of Zn2+ cations for Pb2+ cations. The cation exchange is anisotropic starting at one edge of the nanocrystals and proceeds along the (111) direction producing a sharp interface at a (111) crystallographic plane. Instead of spherical core/shell structures, we produced and studied quasi-spherical CdS/PbS and CdSe/PbSe Janus-type heterostructures. Nontrivial PL behavior was observed from the CdS(e)/PbS(e) heterostructures as the Pb:Cd ratio is increased.
Keywords: quantum dots; heterostructures; cation-exchange reactions; synthesis; lead chalcogenide